Conceptualizing Individual Agency in the Transition from School to Work: A Social-Ecological Developmental Perspective - Ingrid Schoon; Jutta Heckhausen (Adolescent Research Review, 2019)
This article addresses the ongoing debate on the role of agency and structure in shaping the transition from school to work. Drawing on theories of life-course sociology and life-span psychology an integrated social-ecological developmental approach is presented, conceptualizing individual agency as a relational and intentional process that evolves through interactions with the wider socio-cultural context. Agency is understood as a multi-dimensional construct, influenced by multiple proximal and distal social circumstances that channel the manifestation of agency by offering distinct transition pathways. The article specifies the ways how social structures support and constrain the development of agency, and asks if individual agency can overcome social constraints, and to what extent and in what circumstances can agency be most effective? It is argued that agency is most influential (a) when social structures are flexible, enabling switching between tracks; (b) during critical windows of opportunity, such as during transitions from one educational track to another or from education into paid employment; (c) in situations when individuals leave a pre-structured path; (d) when intentions are closely matched to individual competencies; and (e) when socio-economic disadvantage is not overpowering. The analysis presented in this paper should enable researchers to expand and deepen their understanding of the role of structure and agency in shaping school-to-work transitions and inform empirical research on the topic.
Keywords: 330; agency; structure; school-to-work transition (SWT); life course; expectancy-value theory; action-phase model